“Mande notícias do mundo de lá...”: discurso proferido na Colação de Grau da 1ª Turma do Curso TPICS/ENN/UFRN - Estácio, Mércia Maria de Santi (Revista Inter-Legere, 2013)
“SEND NEWS OF THE WORLD THERE ..." speech at the graduation of the 1st Class Course TPICS / ENN / UFRN